HYDRODYNAMICS OF SWIRLING FLUIDIZED BED - VENKITESWARAN, VINOD KUMAR (2013)
The Swirling Fluidized Bed (SFB) being a newer verswn of the well-known bubbling fluidized bed, a physical insight into its working, operating regimes and relationship with various aspects need to be investigated. Although some studies have been conducted on SFB in the past, a thorough understanding of the science of the process is yet to be arrived at. Since previous studies on SFB show promise of a highly effective alternative for contemporary techniques and immense potential for commercialization, a comprehensive study on the various aspects controlling the hydrodynamics of the swirling fluidized bed has been carried out.